Global klimapolitik: Fra Bali til Paris - Skovgaard, Jakob; Blaxekjær, Lau (Politik, 2013)
This paper analyses the international climate negotiations from the so-called 2007 Bali Roadmap over the 2009 breakdown in negotiations at the UN climate summit COP15 to the following COP meetings with a focus on central issues and tendencies. e analysis is structured by applying the concepts of content and process as empirical and heuristic tools. is is used as the point of departure to analyse the road to Paris, where COP21 will be held in 2015 with the stated goal of reaching a global agreement corresponding to the previous goal of COP15, only now covering the period from 2020 onwards. e paper concludes that the recent COPs can be characterised by three overlapping discussions: How parties interpret and seek to imple- ment the principle of common but di erentiated responsibility, the principle of equity, as well as the question of real e ects of actions to mitigate climate change.